2016
DOI: 10.1016/s0140-6736(16)30956-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of early lens extraction for the treatment of primary angle-closure glaucoma (EAGLE): a randomised controlled trial

Abstract: Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
298
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(309 citation statements)
references
References 20 publications
6
298
0
5
Order By: Relevance
“…Clear-lens extraction was performed on 208 and 211 had standard care of LPI. Clear-lens extraction showed greater efficacy and was more cost-effective than LPI [12]. Medicare allowable for LPI in our ASC is $394.93 and $1406.13 for CE.…”
Section: Discussionmentioning
confidence: 73%
“…Clear-lens extraction was performed on 208 and 211 had standard care of LPI. Clear-lens extraction showed greater efficacy and was more cost-effective than LPI [12]. Medicare allowable for LPI in our ASC is $394.93 and $1406.13 for CE.…”
Section: Discussionmentioning
confidence: 73%
“…Significantly fewer patients in this group needed any treatment to control IOP and fewer needed glaucoma medications than patients who received standard care. The authors suggested that clear lens extraction should be considered as an option for first-line treatment [20]. Economic findings from the EAGLE study indicated that lens extraction has a 67-89% chance of being cost effective at three years (fewer subsequent procedures including repeat LPI, lens extraction or glaucoma surgery, and lower medication use), and it may be cost saving by 10 years [21].…”
Section: Discussionmentioning
confidence: 99%
“…Liegt keine visuell signifikante Katarakt vor, ist hingegen umstritten, ob und wann eine solche Intervention durchgeführt werden sollte [47]. Eine aktuelle randomisierte, kontrollierte Studie ergab, dass die frühe Linsenextraktion sinnvoll sein könnte, wenn die Linse eine signifikante Komponente des Winkelverschlusses darstellt [48]. Der Verlust der Akkommodation in diesem Szenario, insbesondere bei vergleichsweise jungen Patienten, muss hierbei berücksichtigt werden.…”
Section: Therapieoptionenunclassified
“…Hierzu zählen ein hoher AID, ein flacher Vorderkammerraum, das Floppy-Iris-Syndrom nach Irisischämie, posteriore Synechien, eine massige Linse, schlaffe Zonulafasern und das Risiko eines malignen Glaukoms [48]. Bei einem unerfahrenen Operateur kann die Linsenextraktion in diesen Augen oft zu potenziell verheerenden Komplikationen führen, einschließlich einer posterioren Kapselruptur, eines abstürzenden Linsenkerns oder einer suprachoroidalen Blutung.…”
Section: Therapieoptionenunclassified